125*5(3x)=27*27(x)

Simple and best practice solution for 125*5(3x)=27*27(x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 125*5(3x)=27*27(x) equation:


Simplifying
125 * 5(3x) = 27 * 27(x)

Remove parenthesis around (3x)
125 * 5 * 3x = 27 * 27(x)

Multiply 125 * 5
625 * 3x = 27 * 27(x)

Multiply 625 * 3
1875x = 27 * 27(x)

Multiply 27 * 27
1875x = 729x

Solving
1875x = 729x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-729x' to each side of the equation.
1875x + -729x = 729x + -729x

Combine like terms: 1875x + -729x = 1146x
1146x = 729x + -729x

Combine like terms: 729x + -729x = 0
1146x = 0

Divide each side by '1146'.
x = 0

Simplifying
x = 0

See similar equations:

| 0.35(2y-1)=-0.7y | | d+7=-7 | | y-34+12+3=14 | | 2x+24=.29x | | (x+10)(2x)(2x-30)= | | -2(-3k+4)-7=15 | | -3(x-4)=2(x+1) | | 22.5x-15=12 | | 4n-6=8+2n | | 9=7-2c | | 125*5(3x)=27*27x | | 8x+7=4x+47 | | x+10-18=-5 | | 45+35x=20+40x | | y=2mx+7b | | 2(3x+1)-3(-4x+1)=20x-19 | | X+17=12-19 | | 4x^2+5=2y | | -16=x+(-22) | | 4n-5=-17 | | -8(5n+7)=40-8n | | 4x-6+42=90 | | 2[d-(4d+13)+3]=2(d+10) | | 22.5x-15.0=12 | | 2y(6z-x)= | | 48+x=4 | | -5y-5(5z-3y)+3= | | 10p=170 | | 5-(2x+5)=-7 | | 18=0.5 | | -15.5n+17.23+5n=-12.8n-11.06 | | [t+6]=4 |

Equations solver categories